Bioaccumulation of Toxic Heavy Metals in the Edible Fishes of Eastern Kolkata Wetlands (EKW), the Designated Ramsar Site of West Bengal, India - Joystu Dutta; Goutam Roy Choudhary; Abhijit Mitra (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2017)
This paper attempts to conduct a survey in the commonly edible finfish species collected from EKW during three seasons of 2016. Eastern Kolkata Wetland (EKW) is the only designated Ramsar Site in West Bengal The wetland with an area of about 12, 500 hectares act as natural kidneys and is also the natural sewage treatment plant for the ever increasing city of Kolkata. This multiple-use wetland lies on the eastern fringes of the city and includes a garbage dump known as Dhapa Square Mile, a mosaic of vegetable fields, a series of 300-odd fishponds connected by major and secondary canals, paddy fields, wholesale markets, a few roads, and 43 villages with an ever increasing population. The fishponds produce some 13,000 tons of fi sh annually, whose yield is at 2-4 times higher than average fish ponds, is among the best of any freshwater pisciculture in the country. Some 150 tons of vegetables per day are harvested from small-scale plots irrigated with waste water. It is essential to conduct a survey of the bioaccumulation pattern of toxic heavy metals such as Pb, Cd, Cr, and Hg in the finfish species commonly consumed by people in this region. The survey was carried out during three seasons of 2016. The accumulated toxic heavy metals were found in the order Pb > Cd > Cr > Hg. The seasonal order was Monsoon > Postmonsoon > Premonsoon. The seasonal variation might be the effect of monsoonal runoff from the highly urbanized and industrial city of Kolkata that convey huge quantum of effluents in the water of EKW. Such study has immense importance as fi shes are consumed by a large percentage of the people in and around Kolkata. This study would also provide a roadmap for researchers and  policymakers to identify and implement effective and sustainable measures to counteract the increasing trends of pollution levels in natural ecosystems.